Admission of patients with STEMI since the outbreak of the COVID-19 pandemic: a survey by the European Society of Cardiology - Pessoa-Amorim, Guilherme; Camm, Christian F.; Gajendragadkar, Parag; De Maria, Giovanni Luigi; Arsac, Celine; Laroche, Cecile; Zamorano, José Luis; Weidinger, Franz; Achenbach, Stephan; Maggioni, Aldo P.; Gale, Chris P.; Poppas, Athena; et al. (European Heart Journal - Quality of Care and Clinical Outcomes, 2020)
AIMS: The COVID-19 pandemic required a significant redeployment of worldwide healthcare resources. Fear of infection, national lockdowns and altered healthcare priorities have the potential to impact utilisation of healthcare resources for non-communicable diseases. To survey health professionals' views of the impact of the COVID-19 pandemic on the rate and timing of admission of patients with ST-elevation myocardial infarction (STEMI), the European Society of Cardiology (ESC) administered an internet-based questionnaire to cardiologists and cardiovascular nurses across 6 continents. METHODS AND RESULTS: 3101 responses were received from 141 countries across 6 continents. 88.3% responded that their country was in "total lockdown" and 7.1% in partial lockdown. 78.8% responded that the number of patients presenting with STEMI was reduced since the coronavirus outbreak and 65.2% indicated that the reduction in STEMI presentations was >40%. Approximately 60% of all respondents reported that STEMI patients presented later than usual and 58.5% that >40% of STEMI patients admitted to hospital presented beyond the optimal window for primary percutaneous intervention (PCI) or thrombolysis. Independent predictors of the reported higher rate of delayed STEMI presentation were a country in total lockdown, >100 COVID-19 cases admitted locally, and the complete restructuring of the local cardiology service. CONCLUSION: The survey indicates that the impact of COVID-19 on STEMI presentations is likely to be substantial, with both lower presentations and a higher rate of delayed presentations occurring. This has potentially important ramifications for future healthcare and policy planning in the event of further waves of this pandemic.
CRIS-Team Scopus Importer:2020-08-07
Keywords: COVID-19; European Society of Cardiology; ST-elevation myocardial infarction